How is leadership experienced in joy-of-life-nursing-homes compared to ordinary nursing homes: a qualitative study - Beate André; Frode F. Jacobsen; Gørill Haugan (BMC, 2022)
Abstract Background Nursing homes are under strong pressure to provide good care to the patients. In Norway, municipalities have applied the 'Joy-of-Life-Nursing-Homes' (JoLNH) strategy which is based on a health-promoting approach building on the older persons' resources. Meanwhile job satisfaction is closely related to less intention to leave, less turnover and reduced sick leave. The knowledge about adjustable influences related with job satisfaction might help nursing home leaders to minimize turnover and preserve high quality of care. This study explores leadership in Norwegian nursing homes with and without implementation of JoLNH: How does leadership influence the work environment and how is leadership experienced in JoLNH compared to ordinary Nursing Homes? Method We used a qualitative approach and interviewed 19 health care personnel working in nursing homes in two Norwegian municipalities. The analysis was conducted following Kvale's approach to qualitative analysis. Results The main categories after the data condensing were [1] the importance of leadership, and [2] the importance of leadership for the work environment in a municipality with (a) and without (b) an implementation of the JoLNH strategy. Conclusions The health care personnel in the municipality with an implementation of JoLNH emphasize that the leader's influence may lead to increased motivation among the staff and better control of changes and implementation processes. Our findings may indicate that the employee from a JoLNH municipality experience a more trustful relationship to the leader.